Optimal Surgery Type and Adjuvant Therapy for T1N0M0 Lung Large Cell Neuroendocrine Carcinoma - Peng, Kunwei; Cao, Huijiao; You, Yafei; He, Wenzhuo; Jiang, Chang; Wang, Lei; Jin, Yanan; Xia, Liangping (Frontiers in Oncology, 2021)
Abstract Background: The appropriate treatment strategy for T1N0M0 lung large cell neuroendocrine carcinoma(LCNEC) was not well illustrated. We evaluated the efficacy of different surgery types and adjuvant therapy on patients with T1N0M0 LCNEC. Methods: Patients diagnosed T1N0M0 LCNEC from 2004 to 2016 were identified in the surveillance, epidemiology, and end results (SEER) database. Clinical characteristics, treatment and survival data were collected. The efficacy of surgery type and adjuvant therapy stratified by tumor size was assessed. Overall survival(OS) was evaluated by the Kaplan-Meier method, and relevant survival variables were identified by the Cox proportional hazard model. Results: From 2004 to 2016, 425 patients were included in this study, 253 (59.5%) patients received lobectomy, and 236 (55.5%) patients had 4 or more lymph nodes removed. Patients received lobectomy had better survival than those received sublobar resection(P=0.000). No matter tumor size less than 2 cm or 2 to 3 cm, lobectomy was significantly prolonged survival. Compared with no lymph nodes removed, lymph nodes dissection was associated with more remarkable OS(P<0.000). 4 or more regional lymph nodes dissection predicted better OS compared with 1 to 3 regional lymph nodes dissection(P=0.014). After surgery, adjuvant chemotherapy did not contribute to extended survival in patients with tumor less than 2 cm(P=0.658), and possibly for tumor 2 to 3 cm(P=0.082). Multivariate analysis showed that age and lobectomy were independent prognostic factors(P=0.000). Conclusion: Our results suggest that lobectomy and lymph nodes dissection were associated with significantly better survival. Extensive regional lymph node dissection(4 or more) was more effective in prolonging survival than 1 to 3 lymph nodes dissection. Adjuvant chemotherapy was not associated with extended survival for tumor less than 2 cm, and possibly for tumor 2 to 3 cm.